Spatial Distribution of Energy of Subinertial Baroclinic Motions in the Baltic Sea - Kurkin, Andrey; Rybin, Artem; Soomere, Tarmo; Kurkina, Oxana; Rouvinskaya, Ekaterina (Frontiers in Earth Science, 2020)
We explore the basic properties of the “climate” of the field of subinertial motions with periods of 2–12 days in the Baltic Sea. The calculations are performed using the output of the Rossby Center Ocean Model RCO with a spatial resolution of 2 nautical miles for 1961–2005. The field of such motions in the Baltic Sea is strongly asymmetric, with much more energy present in the eastern regions of the sea. Spatial distributions of 5-yr average amplitudes of fluctuations of the main and seasonal pycnocline, near-bottom velocity and kinetic and potential energy reflect this asymmetry and also exhibit extensive variability on scales of a few tens of kilometers. The majority of potential energy of such motions is concentrated in a narrow nearshore strip of the sea with a typical width of <20 km. The largest values of kinetic energy occur along the gently sloping seabed at intermediate depths. The areas of maximum of absolute nearbed velocities only partially match similar areas hosting very large kinetic energy or strong fluctuations of the location of the pycnocline. Both the major properties and spatial details of the discussed distributions exhibit almost no difference for the years 1961–1965 and 2000–2005, except for the maximum seabed velocities that are somewhat larger in 2000–2005 apparently because of exceptional storms in 2001 and 2005.